ARCHITECTURAL EXPRESSIVENESS OF FACADES OF TERRACED RESIDENTIAL BUILDINGS - Honcharyk, Andrii (Theory and practice of design, 2025)
This study explores the formation of architectural expression in the facades of townhouses within the context of contemporary urban development. It analyzes compositional approaches, textural and color techniques, as well as the use of modern materials and façade technologies. The research highlights the role of the façade as a carrier of architectural identity and its impact on residents’ psychological comfort and interaction with the surrounding environment. Key challenges are outlined, including the standardization of housing development, the loss of individual character in residential buildings, and the need to combine aesthetics with functionality and energy efficiency. The purpose of the study is to identify effective architectural strategies for creating expressive façade imagery in townhouses, considering current requirements for aesthetics, technological advancement, energy efficiency, and environmental individualization. Methodology. The research is based on the analysis of domestic and international scientific sources, examples of contemporary design practices, and completed projects. Comparative and typological methods are applied to evaluate façade architectural solutions in terms of their expressiveness, functionality, and adaptability to modern challenges. Results. The study reveals that architectural expressiveness of facades is achieved through a combination of well-considered compositional principles, individualized color and material solutions, modularity, and adaptive façade systems. It is determined that effective design of townhouse facades requires a balance between aesthetics, technology, contextual sensitivity, and the needs of residents. Scientific novelty. The study refines approaches to forming the architectural identity of facades in the townhouse housing segment. It proposes a comprehensive method that incorporates modern design, material-technological, and compositional solutions to enhance architectural expression in accordance with sustainable development principles. Practical relevance. The findings can be applied in the development of design solutions in the field of low-rise residential construction, particularly in adapting standard projects to meet requirements of architectural identity, aesthetic appeal, and harmonious integration into the environment.